PENGARUH KEKUATAN TARIK DAN KEKUATAN BENDING KOMPOSIT HYBRID DAN NON-HYBRID MENGGUNAKAN METODE VACUUM BAGGING - Fadhlah Hazhari (Politeknik Negeri Ketapang, 2022)
Composites can be arranged using natural fibers, such as jute fibers then combined with woven roving. Jute fiber is an organic waste that is widely obtained as a burlap sack hole. Synthetic fibers have the advantages i fibers that are strong, corrosion resistant, heat resistant and easy mass produce. Making composites can be done several methods, one which is using vacuum bagging method with a technique using pressure direct resin fibers. researcher's goal is to determine characteristics tensile tests and bending tests using vaccum bagging. (hybrid) In form a yield value 62.94 Mpa and tensil 85.9. Non hybrid fibers can be yielded 28.7 Mpa and tensile 32.9 Mpa. While bending test on hybrid fibers obtained bending strength with a value of 1,126.96 MPa. In non-hybrid fibers, bending strength results were obtained with a value of 643.30Mpa.